Etnopedagogi dalam Kearifan Lokal Rebo Wekasan: Integrasi Nilai Silaturahmi dan Karakter Berbagi pada Pendidikan Dasar - Riani, Tresna; Suhelvi, Suhelvi; Halimatussa’adah, Neneng; Rosidin, Odien (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
This study aims to explore the ethnopedagogical values embedded in the Rebo Wekasan tradition and their relevance to character education in elementary schools. Rebo Wekasan, held on the last Wednesday of Safar, is understood by the community as a collective effort through prayer, sunnah prayer, almsgiving, and communal gatherings to ward off misfortune. The research -kemployed a qualitative descriptive approach with semi-structured interviews involving religious leaders, cultural practitioners, and local residents. Data were analyzed using Miles and Huberman’s interactive model. Findings reveal that the tradition embodies religious values (faith and prayer), social values (solidarity, cooperation, sharing), and cultural values (social cohesion and preservation). The study concludes that Rebo Wekasan’s values can be integrated into Islamic Education and Civic Education curricula as a local wisdom-based learning source to strengthen students’ character formation.